Plastic Impregnated Lignocellulosic Composite - M.B. Hanis Azimah;; I. Anis Nadhirah;; A. Alida (Universiti Sains Islam Malaysia, 2024)
Plastic impregnated lignocellulosic polymer composites are supported new generation reinforcing materials. Hence, lignocelluloses make composite become more environmentally friendly. This work is focused on the fabrication and analysis of the lignocellulosic reinforced thermoplastic materials. The aim of the research project is to develop eco-composite based polymer and improve ineffective lignocelluloses to an , incredibly valuable products. Fabrication of lignocellulosic polymer composite was carried out by impregnating the polymer substrate with a lingocelluloses fibre and undergoes normal as well as vacuum pressure to produce the samples. Furthermore. due to the strong lignocelluloses structure, these fibres possess good strength properties compared to other reinforcing materials. These liqnocelluloses materials offered low cost raw materials, easy availability, non-toxicity and required simple production equipments.